Dual Pathways Linking Trait Negative Affect to Employee Creativity - Yoon, Hye Jung (Journal of Ecohumanism, 2024)
Previous studies have reported inconsistent findings regarding the impact of negative affectivity on employee creativity. To accurately capture the influence of negative affect in organizational environments, this research investigates the relationship between trait negative affectivity and employee creativity. This study also proposes a dual-pathway theoretical framework, encompassing both positive and negative paths of trait negative affect in an integrated model. Drawing on mood-as-input theory and conservation of resources theory, this study explores the mediating effects of (1) needs for problem reframing and (2) impression management motivation in linking the relationship between negative affect and employee creativity. A survey was conducted with 244 full-time employees working in various industries. As a result of structural equation modeling analyses, the dual pathways connecting negative affectivity to employee creativity were found to be empirically supported. According to the statistical results, negative affectivity exhibited a positive indirect effect on employee creativity via needs for problem reframing, while it had a negative indirect effect through impression management motivation. The implications and limitations of this study are discussed.